Myśl ekonomiczna Gandhiego i jej rola w życiu współczesnych Indii - Justyński, Janusz (Wydział Prawa i Administracji UAM, 1975)
In the last thirty years the influence of Gandhi's ideology has decreased. However nearly all the political groups, The Indian National Congress, all the oposition parties (excluding two communist parties of India), declare their desire to carry on Gandhà's ideology. The reason for it is quite obvious; none of India's political parties is willing to give up the great force for the country folk such as gandhism is. Everybody can find something for himself in Gandhi's compromising and ambiguous ideas which can be well used by opposite political parties for their own good in their political struggle. Declarative acceptation of Gandhi's ideology cannot give a right picture of how large is the range of his influence on the present economic life in India. Therefore, it is essential to analyse Gandhi's economic doctrine (although he wasn't an economist), and compare it with a basic social-economical occurrence in life of a country and on this foundation try to define Gandhi's influence on the contemporary life of India. The article contains two basic chapters: about foundations of Gandhi's economic thought, specially his criticism of the Western civilisation, great industry and economic imperialism, and economic grounds of s w a r a j and s a r v o d a y a , the second one is about the role of gandhism in social-economic and political life in contemporary India, Vinoba Bhave activity, and finally it tries to estimate the real role of Gandhism in the economic life of Independent India.
Gandhi's Economic Thought and its Function in the Contemporary India